Antimicrobial, Antibiofilm, and Anti-persister Activities of Penfluridol Against Staphylococcus aureus - Liu, Yaqian; She, Pengfei; Xu, Lanlan; Chen, Lihua; Li, Yimin; Liu, Shasha; Li, Zehao; Hussain, Zubair; Wu, Yong (Frontiers in Microbiology, 2021)
Staphylococcus aureus has increasingly attracted global attention as a major opportunistic human pathogen owing to the emergence of biofilms and persisters that are known to increase its antibiotic resistance. However, there are still no effective antimicrobial agents in clinical settings. This study investigated the antimicrobial activity of penfluridol (PF), a long-acting antipsychotic drug, against S. aureus and its clinical isolates via drug repurposing. PF exhibited strong bactericidal activity against S. aureus, with a minimum inhibitory concentration and minimum bactericidal concentration of 4–8 µg/mL and 16–32 µg/mL, respectively. PF could significantly inhibit biofilm formation and eradicate 24 h preformed biofilms of S. aureus in a dose-dependent manner. Furthermore, PF could effectively kill methicillin-resistant Staphylococcus aureus (MRSA) persister cells and demonstrated considerable efficacy in a mouse model of subcutaneous abscess, skin wound infection, and acute peritonitis caused by MRSA. Notably, PF exerted almost no hemolysis activity on human erythrocytes, with limited cytotoxicity and low tendency to cause resistance. Additionally, PF induced bacterial membrane permeability and ATP release and further caused membrane disruption, which may be the underlying antibacterial mechanism of PF. In summary, our findings suggest that PF has the potential to serve as a novel antimicrobial agent against S. aureus biofilm- or persister-related infections.